Ultrasound-Assisted Extraction of L-Tryptophan from Chamomile Flower: Method Development and Application for Flower Parts Characterization and Varietal Difference - Oktaviani, Nurul Mutmainah Diah; Larasati, Intan Dewi; Nugroho, Andreas Wahyu; Setyaningsih, Widiastuti; Palma, Miguel (Trends in Sciences, 2024)
Chamomile has been widely used as a functional tea due to its effects on several neurohormones, some of which are related to tryptophan. An analytical ultrasound-assisted extraction (UAE) technique was successfully optimized and validated to determine tryptophan levels in chamomile flowers. A Box-Behnken design, in conjunction with response surface methodology, was conducted based on 3 factors and 3 levels: Temperature (x1; 30, 50, and 70 °C), solvent composition (x2; 0, 40, and 80% methanol in water), and ultrasonic power (x3; 20, 60, and 100%). The main (x2) and quadratic effect of solvent (x2x2); quadratic of temperature (x1x1) and ultrasonic power (x3x3); also, the interaction of solvent-ultrasonic power (x2x3) and temperature-ultrasonic power (x1x3), significantly affected (p < 0.05) the level of L-tryptophan in the extracts. Optimum extraction conditions were achieved by applying a temperature of 54 °C for 15 min using 17% methanol in water and 69% ultrasonic power. A high recovery (94.26%) was achieved with 2 extraction cycles. The coefficient of variation (CV) demonstrated that the developed method had a satisfactory level of precision (CV < 5%) for repeatability and intermediate precision. To check the applicability of the method, the parts of 2 types of chamomile flowers (German and Roman) were evaluated. This method was successfully applied to characterize chamomile flowers based on L-tryptophan levels. HIGHLIGHTS A novel ultrasound-assisted extraction method was successfully optimized and validated for extracting L-tryptophan from chamomile flowers Solvent composition was the most influential factor in extracting L-tryptophan from chamomile flowers The level of L-tryptophan in ray and disc florets part of Roman dan German chamomile was revealed for the first time GRAPHICAL ABSTRACT